Obesity related risk of sudden cardiac death in the atherosclerosis risk in communities study. Issue 3 (19th November 2014) - Adabag, Selcuk; Huxley, Rachel R; Lopez, Faye L; Chen, Lin Y; Sotoodehnia, Nona; Siscovick, David; Deo, Rajat; Konety, Suma; Alonso, Alvaro; Folsom, Aaron R
Abstract : Objective: To examine the association of body mass index (BMI), waist circumference (WC) and waist hip ratio (WHR) with sudden cardiac death (SCD) in community dwelling individuals. Methods: Data from a multicentre, prospective, cohort study of 14 941 men and women (African American, and white), aged 45–64 years, participating in the Atherosclerosis Risk in Communities study was analysed. Obesity measures were assessed at baseline (1987–1989). SCD was adjudicated by a committee. Results: At enrolment mean±SD age of the participants was 54±6 years (55% female; 26% African American). During 12.6±2.5 years of follow-up, 253 SCD occurred (incidence rate 1.34/100 person-years). The association between obesity and SCD differed by smoking status (interaction p≤0.01). In models adjusting for age, sex, race, study centre and education level, SCD risk was positively associated (p<0.001) with BMI, WC and WHR in non-smokers, but not in smokers. WHR was more strongly associated with SCD in non-smokers than was BMI or WC (HR per SD increment (95% CI) 2.00 (1.65 to 2.42); 1.34 (1.15 to 1.56) and 1.49 (1.28 to 1.74), respectively). After adjustment for potential mediators (hypertension, diabetes, lipid profile, prevalent coronary heart disease, heart failure, and LV hypertrophy), non-smokers in the highest WHR category (>0.95 in women; >1.01 in men) had double the risk of SCD (HR 2.03, 95% CI 1.19 to 3.46; incidence rate 1.43/1000 person-years) versus those with normal WHR. Conclusions: General obesity is associated with increased risk of SCD in middle-aged, non-smoking individuals, mediated by traditional cardiovascular risk factors. Central obesity, however, is independently associated with SCD by pathways that remain to be elucidated.